From ‘Lockdown’ to Letdown: Students’ Perception of E-learning amid the COVID-19 Outbreak - Krishnapatria, Kriswanda (ELT in Focus, 2020)
This research is motivated by the need of exploring the students’ perception of e-learning implementation of two English language subjects in the time of COVID-19 pandemic. This research is descriptive, and data were collected through online questionnaire. The participants were students of International Business of Padjadjaran University taking English for Business Purposes and Speaking for Business Purposes courses. The result of the analysis shows that 100% of students participated in e-learning, and 96.4% have accessibility in online learning. However, only 56% expressed satisfaction with the implementation of e-learning.As a result, the students’ perceptions of e-learning are somewhat fruitful; further, it can promote flexibility, offer personalisation where learners can choose their learning path and pace. Fair assessment of students’ perception in e-learning may grant a good precedent in the implementation of full online learning due to physical isolation caused by the COVID-19 pandemic, which alternatively can be done with the method of blended learning in the New Normal.